2005
DOI: 10.1111/j.1525-1438.2005.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted vaginal hysterectomy versus abdominal hysterectomy in patients with stage I and II endometrial cancer

Abstract: The purpose of this study was to evaluate and compare the outcomes of laparoscopic surgery with those of conventional abdominal surgery in patients with early endometrial cancer. From 1997 to 2003, 79 patients underwent laparoscopic-assisted vaginal hysterectomy with or without lymphadenectomy. Laparoscopy was performed on patients deemed clinical stage I in preoperative studies. Of the 79 patients, 74 found to be surgical stage I or II were enrolled in the comparative study. As a control group, we selected 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
1
21
1
5
Order By: Relevance
“…The mean hospital stay of our patients was longer than that reported in other studies, most likely because most Korean patients only want to be discharged after a complete recovery, including the removal of any drainage tubes and stitches and improvement in their general health condition, and the Korean medical insurance system covers this (3).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The mean hospital stay of our patients was longer than that reported in other studies, most likely because most Korean patients only want to be discharged after a complete recovery, including the removal of any drainage tubes and stitches and improvement in their general health condition, and the Korean medical insurance system covers this (3).…”
Section: Discussioncontrasting
confidence: 48%
“…Recently, due to advances in the use of laparoscopic surgical techniques, laparoscopy has been reportedly used for both the exact staging and the effective treatment of endometrial carcinoma. It has also been demonstrated that laparoscopic surgery results in shorter hospital stays, earlier recovery times, and a better quality of life (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the largest randomized, controlled trial (Gynecologic Oncology Group (GOG), LAP 2 trial) comparing laparoscopy with laparotomy for surgical staging of endometrial cancer, the rate of conversion to laparotomy after initially being assigned to laparoscopic surgery was 25 17,23,26,47]. In series where experienced surgeons performed consecutive laparoscopic surgery for all patients with earlystage endometrial cancer, regardless of age, body mass index, uterine size, or history of prior surgery, the conversion rate was only 3-5 % [46•, 48], and only 7 % for morbidly obese patients [46•].…”
Section: Feasibility Of Laparoscopic Surgerymentioning
confidence: 99%
“…Indeed, whilst endometrial cancer is the first gynecologic cancer to be treated laparoscopically, a laparoscopic approach also is being used for the surgical management of malignant disease. Following the first report on the use of laparoscopic surgery for endometrial cancer by Childers et al [12], the feasibility, safety, and efficacy of laparoscopic surgery in the surgical management of endometrial cancer has been reported in numerous retrospective studies [13][14][15][16][17][18][19][20][21][22][23][24][25], prospective nonrandomized studies [26][27][28][29], or randomized, controlled trials (RCTs) [30][31][32][33][34][35][36][37][38][39][40][41][42]43 This review provides an update on the role of laparoscopic surgery for the surgical management of endometrial cancer with particular emphasis on feasibility, safety, and efficacy based on the results of randomized, controlled trials comparing laparoscopy and laparotomy for surgical staging of endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies since have shown that this approach is associated with a shorter hospitalisation, faster recovery, lower complications when compared to open surgery. 5,17,18 . Meta analysis of 17 prospective and retrospective studies showed that laparoscopic approach to surgical treatment for women with endometrial cancer had lower complications and no significant difference in recurrent rates or disease free survival 19,20. …”
Section: Laparoscopic Hysterectomy With Pelvic Lymphadenectomymentioning
confidence: 99%